The Effect of Google Slide Learning Media on the Chronological Thinking Ability of Grade XI Students of SMA Negeri 6 Kota Serang: Pengaruh Media Pembelajaran Google Slide Terhadap Kemampuan Berpikir Kronologis Siswa Kelas XI di SMA Negeri 6 Kota Serang - Sifa Tantriani; Yuni Maryuni; Arif Permana Putra (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to determine the effect of Google Slide learning media on the chronological thinking ability of Grade XI students at SMA Negeri 6 Kota Serang. The method used in this research is a quantitative quasi-experimental method using a non-equivalent control group design. The research was conducted on two clasess, namely XI-A3 with 44 students as the experimental class, and XI-A2 with 42 students as the control class. The results of the study are as follows: (1) there is an effect of using Google Slide learning media on the chronological thinking ability of Grade XI students at SMA Negeri 6 Kota Serang. The hypothesis testing using the two-tailed t-test with the polled variance formula using Ms. Excel obtained a t-count value of 0.45 ≥ t-table value of 1.66 with a significance level of 0.05, so H0 is rejected and H1 is accepted. (2) The chronological thinking ability of students who use Google Slide learning media is higher than that of students who use Canva. The average post-test score of the experimental class is 76.93, and the control class is 70.05. This shows that the experimental class has a higher average than the control class. This is not separated from the advantages of Google Slides media which are interactive, easily accessible online, and support effective collaboration and visualization of learning materials. Google Slides also enable teachers to embed relevant images, videos, animations, and links, thereby increasing students' interest and understanding of lesson materials, especially in developing chronological thinking ability.